2007
DOI: 10.1523/jneurosci.1847-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Diversity in GABAergic Long-Range Projections from the Hippocampus

Abstract: The formation and recall of sensory, motor, and cognitive representations require coordinated fast communication among multiple cortical areas. Interareal projections are mainly mediated by glutamatergic pyramidal cell projections; only few long-range GABAergic connections have been reported. Using in vivo recording and labeling of single cells and retrograde axonal tracing, we demonstrate novel long-range GABAergic projection neurons in the rat hippocampus: (1) somatostatin-and predominantly mGluR1␣-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
405
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(442 citation statements)
references
References 55 publications
33
405
4
Order By: Relevance
“…The hippocampus CA3 has enriched GABAergic inputs and outputs, whereas the serotoninergic and dopaminergic neurons are scarcely seen. 55,56 Our data further validate that the CA3 accumulation of htau may specifically disrupt the local neural metabolisms and the functions with no influence on serotonergic or dopaminergic input from other brain regions.…”
Section: Discussionsupporting
confidence: 67%
“…The hippocampus CA3 has enriched GABAergic inputs and outputs, whereas the serotoninergic and dopaminergic neurons are scarcely seen. 55,56 Our data further validate that the CA3 accumulation of htau may specifically disrupt the local neural metabolisms and the functions with no influence on serotonergic or dopaminergic input from other brain regions.…”
Section: Discussionsupporting
confidence: 67%
“…Finally, although we have not investigated directly how hippocamposeptal interneurons behave during carbachol oscillations, a previous study has shown that st. oriens-alveus interneurons (which includes some of the neurons projecting to the septum) fire single spikes phase locked to the field in carbachol and are likely activated by recurrent excitation from pyramidal neurons (McMahon et al, 1998;Hajos et al, 2004). An elegant report recently showed that identified st. oriens-alveus hippocamposeptal neurons also fire at low frequency phase locked to theta in vivo and at a similar phase than pyramidal neurons (Jinno et al, 2007). Together, these reports suggest that hippocamposeptal GABA neurons are active during carbachol or theta oscillations and are phase locked to pyramidal cells.…”
Section: Discussionmentioning
confidence: 66%
“…5). SLCs are GABAergic cells that project mainly to the medial septum and possess relatively few local axon collaterals near the cell body (Gulyás et al, 1992;Jinno et al, 2007;Takács et al, 2008). One of the main characteristics of SLCs is that, in contrast to other GABAergic cells in this study, the primary dendrites of SLCs are aligned with and largely restricted to stratum lucidum (and, to a lesser extent, pyramidale), and the dendrites are densely covered with large numbers of dendritic spines (Fig.…”
Section: Specific Description Of Cell Typesmentioning
confidence: 81%
“…2 A, asterisk). Like most other projecting GABAergic cell types (Jinno et al, 2007), the vast majority of SLCs were positive for SOM (24 of 26 tested SLCs) and for NPY (7 of 7), but not for CCK (0 of 17) and PV (0 of 6). Note that we were not able to reliably test for the presence of calretinin, which is another marker for SLCs, most likely because of wash-out of intracellular constituents from postsynaptic cells during the long-lasting somatic recordings.…”
Section: Specific Description Of Cell Typesmentioning
confidence: 89%